Institutional Design of Collaborative Governance in Landslide Disaster Mitigation A Case Study of Sawahlunto City Indonesia - Purnama, Tirza Haqia; Putera, Roni Ekha; Koeswara, Hendri (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
Indonesia is among the world’s most disaster-prone countries, with landslides posing a recurring and high-impact threat, especially in areas with steep terrain and high rainfall. Sawahlunto City in West Sumatra exemplifies this vulnerability, experiencing frequent landslides that result in human, infrastructural, and economic losses. Although various mitigation measures have been introduced, evidence shows that disaster risk reduction depends not only on physical or technical efforts but also on the quality of inter-organizational collaboration and institutional arrangements. This study analyzes the institutional design of collaborative governance in landslide mitigation in Sawahlunto City. Using a qualitative approach, data were gathered through interviews, document reviews, and field observations involving government agencies, community representatives, and relevant stakeholders. The analysis draws on the collaborative governance framework of Ansell and Gash, focusing on institutional design elements such as inclusive participation, exclusive forums, ground rules, and transparency. The findings indicate that collaborative governance mechanisms in Sawahlunto are formally established but function unevenly. Participation is recognized but limited in practice, forums exist yet lack consistency and strategic authority, ground rules are only partly implemented, and transparency varies across agencies. These weaknesses lead to fragmented coordination and reduced mitigation effectiveness. The study concludes that successful disaster mitigation requires not only collaboration but also a coherent, well-structured institutional design that strengthens coordination, accountability, and transparency at the local level.